LEMBAGA PENJAMIN SIMPANAN DALAM LIKUIDASI BANK DI INDONESIA - Hendri Jayadi Pandiangan (Fakultas Hukum Universitas Kristen Indonesia, 2019)
Abstract Legally, LPS has been regulated in Law Number 24 of 2004 concerning the Deposit Insurance Corporation. LPS itself has two functions, namely guaranteeing bank customer deposits and resolving failed bank disputes through liquidation. The process of bank liquidation carried out by the Indonesia Deposit Insurance Corporation through the Liquidation Team of the bank is never complete or leaves a problem for bank customers whose savings are not guaranteed by the Deposit Insurance Corporation. The existence of the Deposit Insurance Agency is also expected to be able to carry out its functions properly in guaranteeing limited bank customer deposits so as to support efforts in stability in the banking sector. Keyword : customer bank; guaranteed; depositsl; LPS.